Something Changed? Imaginaries of Surveillance and (In)security in Transatlantic Science Fiction Novels in the Decade after 9/11 - Murakami Wood, David (Surveillance & Society, 2026)
Based on a formally sampled survey of 120 post-9/11 transatlantic science fiction (SF) novels in English published between 2002–2011 inclusive, and a thematic reading of thirty-eight of these works, this paper analyses the place and treatment of surveillance and security in the culture of Empire. The paper identifies several important post-9/11 interventions in SF and argues that, in comparison to some of the weak mainstream literary work on 9/11 and the Long War, SF has produced some of the bleakest and most insightful responses. However, it also argues that there is a clear transatlantic division between the critical, sharp, and cynical work being produced by British SF authors and the predominantly nostalgic, militaristic, or techno-utopian responses of North American SF authors. It concludes with some reflections not just on the place of post-9/11 surveillance and security in SF but on the continuing relevance of SF to critical surveillance and security studies, and in broader social terms.